Discursive Approach to the Study of Fairy Tales - Tavbayeva G.X. (Genius Journals, 2023)
In this article, an opinion is expressed regarding the specific features and importance of using a discursive approach in the study of fairy tales.
Keywords: folklore; fairy tale; national mentality; discourse